PERANCANGAN MEDIA BELAJAR BERHITUNG UNTUK ANAK TUNANETRA USIA DINI 4-6 TAHUN - Noreen, Noordica Greissaldine; Nurhidayat, Martiyadi; Bahri, Nurul Fitriana (Universitas Bhinneka PGRI, 2023)
Blind students need different support and treatment from normal children during the learning process. Numeracy type learning media specifically made for early blind children, is still not widely found. Blind numeracy learning media that have been circulating such as abacus and abacus have a goal that focuses more on mathematical skills in children at a more mature age. The design is implemented to help blind children to recognize numbers by using learning media adapted to their physical conditions and abilities. The research method used is qualitative descriptive and design methods using User Centered Design which departs from user problems in the problem of using existing learning media. The implementation of learning media was applied at SLB Roudhotul Zannah, from 10 respondents of blind students conducting pre-tests and postests produced as much as 22% pre-test and 33% post-test, then with learning media that has been designed to be very effective to help achieve learning, especially for blind students.